Gene therapies in pediatric ophthalmology - Daruich, Alejandra; Robert, Matthieu P.; Bremond-Gignac, Dominique (Frontiers in Ophthalmology, 2023)
Genetic pediatric eye disease frequently leads to severe vision impairment or blindness. Voretigene neparvovec is the first approved gene therapy for an inherited retinal dystrophy (IRD). Voretigene neparvovec has shown to be well tolerated and safe, with encouraging results in terms of efficacy, mainly when administered early in childhood. While we assist at the first gene therapy available in clinical practice for an IRD, some questions remain to be answered, especially when gene therapy is delivered in young children. We review here the most recent rapports and promising ongoing studies concerning various approaches on gene therapy in pediatric ophthalmology.